PAN EURASIAN EXPERIMENT (PEEX) - A RESEARCH INITIATIVE MEETING THE GRAND CHALLENGES OF THE CHANGING ENVIRONMENT OF THE NORTHERN PAN-EURASIAN ARCTIC-BOREAL AREAS - Hanna K. Lappalainen; Tuukka Petäjä; Joni Kujansuu; Veli-Matti Kerminen; Anatoly Shvidenko; Jaana Bäck; Timo Vesala; Timo Vihma; Gerrit De Leeuw; Antti Lauri; Taina Ruuskanen; Vladimir B. Lapshin; et al. (Geography, Environment, Sustainability, 2014)
The Pan-Eurasian Experiment (PEEX) is a new multidisciplinary, global change research initiative focusing on understanding biosphere-ocean-cryosphere-climate interactions and feedbacks in Arctic and boreal regions in the Northern Eurasian geographical domain. PEEX operates in an integrative way and it aims at solving the major scientific and society relevant questions in many scales using tools from natural and social sciences and economics. The research agenda identifies the most urgent large scale research questions and topics of the land-atmosphere-aquatic-anthropogenic systems and interactions and feedbacks between the systems for the next decades. Furthermore PEEX actively develops and designs a coordinated and coherent ground station network from Europe via Siberia to China and the coastal line of the Arctic Ocean together with a PEEX-modeling platform. PEEX launches a program for educating the next generation of multidisciplinary researcher and technical experts. This expedites the utilization of the new scientific knowledge for producing a more reliable climate change scenarios in regional and global scales, and enables mitigation and adaptation planning of the Northern societies. PEEX gathers together leading European, Russian and Chinese research groups. With a bottom-up approach, over 40 institutes and universities have contributed the PEEX Science Plan from 18 countries. In 2014 the PEEX community prepared Science Plan and initiated conceptual design of the PEEX land-atmosphere observation network and modeling platform. Here we present the PEEX approach as a whole with the specific attention to research agenda and preliminary design of the PEEX research infrastructure.